1986
DOI: 10.1093/nar/14.8.3487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pendant groups at phosphorus on binding properties of d-ApA analogues

Abstract: The interaction of several synthetic analogues of d-ApA with Poly U and Poly dT was examined to explore the effects of substituents at phosphorus on binding properties of oligonucleotides. These analogues contained a bulky, lipophilic group (2,2 ,2-trichloroethoxy or 2,2 ,2-trichloro-1, l-diimethylethoxy) a small, uncharged hydrogen-bonding group (amido), or a cationic phosphoramidate (2-aminoethylamido, protonated in neutral aqueous media) in place of the anionic oxygen of the internucleotide phosphate. As de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 10 publications
3
34
1
Order By: Relevance
“…It is noteworthy that the 9-mer linked only to the dodecanol tail at the 3'-end was also more efficient than the unmodified or acridine-substituted oligomers. Letsinger et al (1986) and Jager et al (1988) have shown that lipophylic substituents may stabilize DNA helical structures. In addition more efficient induction of RNase H cleavage by this oligonucleotide may also result from facilitation of RNase H binding to the hybrid duplex.…”
Section: +1mentioning
confidence: 99%
“…It is noteworthy that the 9-mer linked only to the dodecanol tail at the 3'-end was also more efficient than the unmodified or acridine-substituted oligomers. Letsinger et al (1986) and Jager et al (1988) have shown that lipophylic substituents may stabilize DNA helical structures. In addition more efficient induction of RNase H cleavage by this oligonucleotide may also result from facilitation of RNase H binding to the hybrid duplex.…”
Section: +1mentioning
confidence: 99%
“…Various methods have been developed in an attempt to overcome this problem. Examples include microinjection, surface binding to viral capsids, attaching lipophilic pendant groups, and lipid encapsulation, plus a variety of other methods (Bennett et al, 1992;Chin et al, 1990;Leonetti et al, 1991;Letsinger et al, 1986;McLachlin et al, 1990;Spiller et al, 1998;Takle et al, 1997). With both endogenous uptake and most augmented delivery methods, ODN localize primarily to cellular lysosomes (Bergan et al, 1993;Bergan, 1997;Loke et al, 1989).…”
Section: Introduction I Ntracellular Delivery Of Synthetic Oligonuclementioning
confidence: 99%
“…The product was purified by reversed phase chromatography (elution with linear gradient of methanol in water). Yield, 500 mg (75%) of triethylammonium salt of 6,2 ,3 -tri-N ,O-benzoyl-5 -deoxyadenosin-5 -C-ylphosphonate (15). HR FAB calcd for C 31 H 27 N 5 O 9 P (M + H) + 644.15466, found 644.15553.…”
Section: Partial Deprotection Of 14mentioning
confidence: 99%
“…Therefore, in order to obtain the basic data giving information about the properties of the modified internucleotide linkage, in comparison with other relevant types of linkages, we opted for the study of the thermal stability of duplex-(or triplex-) like structures of the appropriately modified "dimers" (i.e., diribonucleoside monophosphates) with polynucleotides using spectroscopic methods in view of the fact that a variety of modified dinucleoside monophosphates [13] and their enantiomers, [14] neutral phosphotriester [15] and methylphosphonate [16] dimers, and a series of the isopolar internucleotide linkage-modified ApAs [17][18][19][20] have been employed as model compounds to study changes in hybridization properties due to the presence of particular modifications. These studies encouraged us to undertake a study dealing with the following specific tasks: (i) the synthesis of a unique set of phosphonate ApA analogues in ribo and 2 -deoxyribo series with chiral α-hydroxy-phosphonate C3 -O-P-CH(OH)-C4 internucleotide linkage and non-chiral C3 (2 )-O-P-CH 2 -C4 one, (ii) the hybridization of the modified ApAs with polyU, (iii) the nuclear magnetic resonance (NMR) conformational investigation of the modified sugar-phosphate backbone, and (iv) the structural characteristics obtainable on this topics from the evaluation by molecular dynamics simulation (MDS).…”
Section: Introductionmentioning
confidence: 99%